Building back better to avert a learning catastrophe: Estimating learning loss from COVID-19 school shutdowns in Africa and facilitating short-term and long-term learning recovery. (July 2021) - Angrist, Noam; de Barros, Andreas; Bhula, Radhika; Chakera, Shiraz; Cummiskey, Chris; DeStefano, Joseph; Floretta, John; Kaffenberger, Michelle; Piper, Benjamin; Stern, Jonathan
Highlights: Short-term COVID-related learning losses in sub-Saharan Africa are up to one year. The learning loss could accumulate to 2.8 years of long-term lost learning. Targeted instruction and structured pedagogy reforms can mitigate learning losses. Models suggest these reforms could improve pre-COVID learning levels. Crisis presents historic opportunity to enact reforms to address learning crisis. Abstract: We model learning losses due to the COVID-19 pandemic and the potential for cost-effective strategies to build back better. Data from Early Grade Reading Assessments in Ethiopia, Kenya, Liberia, Tanzania, and Uganda suggest half to over a year's worth of learning loss. In modeling losses over time, we found that learning deficits for a child in grade 3 could lead to 2.8 years of lost learning by grade 10. While COVID-19 has stymied learning, bold, learning-focused reform consistent with the literature reviewed in this paper—specifically reform on targeted instruction and structured pedagogy—could improve learning even beyond pre-COVID-19 levels.